Characterization of malaysian non-aflatoxigenic Aspergillus flavus isolates and their potential use as biocontrol agents for aflatoxigenic A. flavus in sweet corn - Rahim, Khan (2020)
This study was intended to morphologically and molecularly characterize and determine the aflatoxigenic and non-aflatoxigenic Aspergillus flavus isolates. Forty isolates of A. flavus were obtained from sweet corn kernels and soil samples collected from Kampong Raja, Rose Valley, Kea, and Klebang farms in Malaysia. They were cultured on potato dextrose agar (PDA), dichloran rose-bengal chloramphenicol (DRBC), A. flavus, and parasiticus agar (AFPA), and coconut cream agar (CCA). Macro-morphological characteristics were determined by observing the colony color, and texture while the micro-morphological characteristics were determined by examining the spore color, size, structure, conidiophore structure, and vesicle shape. The production of aflatoxin was determined by direct visualization of the UV fluorescence of A. flavus colonies on CCA. Aflatoxin was qualitatively detected in 18 (45%) isolates of A. flavus using UV fluorescence screening while the remaining 22 (55%) isolates did not exhibit any aflatoxin production. AFs production by A. flavus was quantitatively analyzed using High-Performance Liquid Chromatography equipped with a fluorescence detector and post-column photochemical reactor. The limits of detection for AFB1, AFB2, AFG1, and AFG2 were 0.072, 0.062, 0.028, and 0.032 ppb, while the limits of quantification were 0.220, 0.189, 0.087, and 0.098 ppb respectively. AFB1 was detected in 24 out of 40 isolates of A. flavus in concentrations ranging between 0.009 and 3.848 ppb. On the other hand, AFG1 was detected in 12 isolates in which two isolates (ARV17, ARV22) exceeded the maximum tolerable limits of 5 ppb (50.687 ppb, 40.434 ppb). AFs content was significantly different (p < 0.05) in A. flavus isolates collected from four different farms. Molecular characterization of A. flavus isolates and detection of AF-producing gene in AF+ was carried out using polymerase chain reaction (PCR). Specific primers, FLA1 and FLA2, were used to amplify the targeted sequence of A. flavus. The isolates were confirmed as A. flavus, exhibiting 100% homology with other reference strains of A. ii flavus on the National Center for Biotechnology Information (NCBI). Multiplex PCR techniques successfully amplified aflP, aflO, and aflR genes. AF-producing genes were detected in 35 strains of A. flavus strains, while the remaining five strains did not exhibit these genes. The efficacy of AF- strains in inhibiting AF+ growth and reducing AFB1 production was assessed. Co-inoculation of sweet corn kernels with AF- and AF+ strains significantly (p < 0.05) reduced the concentrations AFB1 in sweet corn kernels. The concentration of AFB1 detected in the co-inoculated treatments ranged from 0.321 to 1.093 ppb while the reduction of AFB1 in corn kernels ranged from 23% for AKL36- to 79% for AKR5- strain. The AKR5- and AKL34- strains exhibited the maximum AFB1 reductions of 79 and 75% while the AKL36- exhibited a minimum reduction towards AFB1 production. In conclusion, the AKR5- and AKL34- would be suitable candidates as potential biocontrol agents to be used in the sweet cornfield, as they significantly reduced the AFB1 in sweet corn kernels.